Ермітова інтерполяція сумою поліному й степеневої функції - Андруник, В.А.; Малачівський, П.С. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
There are established the necessary and sufficient conditions for existence of Hermite interpolation of function by sum of polynomial and degree with the reproduction of value of derivative function in the end points of interval. The algorithm for determining the parameters of such interpolation is proposed. The application of iterative method to accurate the value of degree index is proved.